Time Irreversibility of Resting-State Activity in the Healthy Brain and Pathology - Zanin, Massimiliano; Güntekin, Bahar; Aktürk, Tuba; Hanoğlu, Lütfü; Papo, David (Frontiers in Physiology, 2020)
Characterizing brain activity at rest is of paramount importance to our understanding both of general principles of brain functioning and of the way brain dynamics is affected in the presence of neurological of psychiatric pathologies. We measured the time-reversal symmetry of spontaneous electroencephalographic brain activity recorded from three groups of patients and their respective control group under two experimental conditions (eyes open and closed). We evaluated differences in time irreversibility in terms of possible underlying physical generating mechanisms. The results showed that resting brain activity is generically time-irreversible at sufﬁciently long time scales, and that brain pathology is generally associated with a reduction in time-asymmetry, albeit with pathology-speciﬁc patterns. The signiﬁcance of these results and their possible dynamical aetiology are discussed. Some implications of the differential modulation of time asymmetry by pathology and experimental condition are examined.